A New Numerical Solution for Prabhakar Fractional Differential Equations Using the Explicit Fractional Adams Method (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces a new way to solve Prabhakar fractional differential equations using an Explicit Fractional Adams Method. These equations are difficult to work with because they have several parameters. The new method, which combines the Explicit Fractional Adams Method with Lagrange interpolation, effectively tackles these difficulties. The paper also includes an analysis to show how well the method works. It provides several examples to demonstrate the method’s effectiveness and compares it with other existing methods. The results show that the proposed method is efficient and easy to use.
Keywords: Lagrange interpolation, Prabhakar fractional, Fractional Differential Equations, Adams Method